Norsk-russisk miljø- og ressursforvaltning i nordområdene - Hønneland, Geir (Nordlit, 2012)
Since the end of the Cold War, a flourishing network of collaboration has grown up between Russia and neighbouring Nordic countries in the European North, especially Norway. The Barents Euro-Arctic Region (BEAR) was established in 1993 by several North European states and regional administrative entities in Norway, Sweden, Finland and Russia. Its aim is to promote relations across the old East-Westdivide in the European North, and enable joint projects in a number of areas, including trade and industry, student exchange and indigenous issues. In addition,Russia and Norway are pursuing various bilateral schemes focused on a particular problem or challenge in the North. One of them is the Joint Norwegian-Russian Fisheries Commission, which manages the valuable fish resources in the Barents Sea.In various bilateral and multilateral partnerships, Norway is working to address the environmental problems on the Kola Peninsula. This article gives a brief overview of these cooperative arrangements.